Reconstructing the use of plumb level from a 19th century clinker boat tradition - Fredrik Leijonhufvud (FORMakademisk, 2023)
Traditionally, vernacular Nordic clinker boats are built without plans or templates. The local boat traditions all have a system of design that was handed over from master to apprentice. In some local traditions, a simple plumb level was used to guide the boatbuilder. The plumb level was placed on the planks of the hull during the build to give them the right angles of inclination in certain parts of the hull. Knowledge of how to use this plumb level is still considered part of living, unbroken traditions in some areas. In some local traditions, however, there are no longer any living tradition bearers that have the knowledge of how this tool was used in the local context. In this contribution, I will discuss how this lost knowledge can be reconstructed using old artefacts as a source material. I am investigating the tradition of building vernacular, clinker-built boats called ‘öka’ for sailing and rowing. This specific boat building tradition was located in the 19th century Stockholm archipelago. The artefacts in this case are preserved boats built in the old tradition and preserved plumb levels from closely related traditions. A central question in this context is to locate the exact positions in the boat that were measured by the plumb level. Working with reverse engineering, the measuring can be performed on preserved boats, but the right places for measuring still must be located to reconstruct the knowledge of how and where to use the tool. Some preserved plumb levels have markings that can be used in this investigation to match the locations and angles in the preserved boats. In this contribution, I will also discuss the possibility of applying the traditional measuring methods used by the old boatbuilders in today´s surveys and reconstructions, not translating the craft object into a digital 3D model or a lines plan.